Changes in Rehmanniae Radix processing and their impact on ovarian hypofunction: potential mechanisms of action - Zhong, Han-Zhi; Mo, Jing; Li, Yan-Xin; Li, Mao-Ya; Wei, Shao-Bin (Frontiers in Pharmacology, 2024)
Objective: This study evaluates the research developments concerning Rehmanniae Radix in ovarian hypofunction diseases. It explores the processing methods of Rehmanniae Radix, the variations in its compounds before and after processing, the mechanism of Rehmanniae Radix and its active compounds in improving ovarian function, and the advancements in clinical applications of traditional Chinese medicine (TCM) compound that include Rehmanniae Radix. Methods: Comprehensive literature search was conducted using databases such as CNKI, China Science and Technology Journal Database, National Science and Technology Library, the Pharmacopoeia of the People's Republic of China, Pubmed, and the Web of Science Database. The search utilized the following Medical Subject Headings (MeSH) and keywords: "Rehmanniae Radix", "Drying Rehmannia Root", "Rehmannia glutinosa", "Rehmanniae Radix Praeparata", "Traditional Chinese Medicine Processing", "Pharmacological Effects", "Ovarian Aging", "Decreased ovarian reserve", "Premature ovarian insufficiency", "Premature Ovarian Failure", "Ovarian hypofunction diseases". Results: The ancient Chinese medical book document various processing techniques for Rehmanniae Radix. Contemporary research has identified changes in its compounds processing and the resultant diverse therapeutic effects. When processed into Rehmanniae Radix Praeparata, it is noted for its ability to invigorate the kidney. TCM compound containing Rehmanniae Radix are frequently used to treat ovarian hypofunction diseases, demonstrating significant clinical effectiveness. The key changes in its compounds processing include cyclic dilute ether terpene glycosides, phenylethanol glycosides, sugars, and 5-hydroxymethylfurfural. Its pharmacological action is primarily linked to the improvement of granulosa cell proliferation, antioxidative and anti-aging properties, and modulation of the immune and inflammatory microenvironment. Furthermore, Rehmanniae Radix also offers therapeutic benefits for cardiovascular and cerebrovascular diseases, osteoporosis and cognitive dysfunction caused by low estrogen levels. Thereby Rehmanniae Radix mitigates both the short-term and long-term health risks associated with ovarian hypofunction diseases. Conclusion: Processed Rehmanniae Radix has shown potential to improve ovarian function, and its compound prescriptions have a definite effect on ovarian dysfunction diseases. Therefore Rehmanniae Radix was garnering interest for both basic and clinical research, with promising application prospects as a future therapeutic agent for ovarian hypofunction diseases. However, further studies on its toxicology and the design of standardized clinical trials are necessary to fully establish its efficacy and safety.